Criticality Assessment of the Life Cycle of Passenger Vehicles Produced in China - Xin Sun; Vanessa Bach; Matthias Finkbeiner; Jianxin Yang (Circular Economy and Sustainability, 2021)
China is globally the largest and a rapidly growing market for electric vehicles. The aim of the paper is to determine challenges related to criticality and environmental impacts of battery electric vehicles and internal combustion engine vehicles, focusing not only on a global but also the Chinese perspective, applying the ESSENZ method, which covers a unique approach to determine criticality aspects as well as integrating life cycle assessment results. Real industry data for vehicles and batteries produced in China was collected. Further, for the criticality assessment, Chinese import patterns are analyzed. The results show that the battery electric vehicle has similar and partly increased environmental impacts compared with the internal combustion engine vehicle. For both, the vehicle cycle contributes to a large proportion in all the environmental impact categories except for global warming. Further, battery electric vehicles show a higher criticality than internal combustion engine vehicles, with tantalum, lithium, and cobalt playing essential roles. In addition, the Chinese-specific results show a lower criticality compared to the global assessment for the considered categories trade barriers and political stability, while again tantalum crude oil and cobalt have high potential supply disruptions. Concluding, battery electric vehicles still face challenges regarding their environmental as well as criticality performance from the whole supply chain both in China and worldwide. One reason is the replacement of the lithium-ion power battery. By enhancing its quality and establishing battery recycling, the impacts of battery electric vehicle would decrease.
Keywords: 330; Criticality; Resources; ESSENZ; Life cycle assessment; Environmental impacts; E-mobility